Deletion of CD137 Ligand Exacerbates Renal and Cutaneous but Alleviates Cerebral Manifestations in Lupus - Mak, Anselm; Dharmadhikari, Bhushan; Kow, Nien Yee; Thamboo, Thomas Paulraj; Tang, Qianqiao; Wong, Lik Wei; Sajikumar, Sreedharan; Wong, Hiu Yi; Schwarz, Herbert (Frontiers in Immunology, 2019)
The CD137 – CD137 ligand (CD137L) costimulatory system is a critical immune checkpoint with pathophysiological implications in autoimmunity. In this study, we investigated the role of CD137L-mediated costimulation on renal, cutaneous and cerebral manifestations in lupus and the underlying immunological mechanism. Lupus-prone C57BL/6lpr-/- (B6.lpr) mice were crossed to C57BL/6.CD137L-/- mice to obtain CD137L-deficient B6.lpr (double knock out (DKO)) mice. We investigated the extent of survival, glomerulonephritis, skin lesions, cerebral demyelination, immune deviation and long-term synaptic plasticity among the two mouse groups. Cytokine levels, frequency of splenic leukocyte subsets and phenotypes were compared between DKO, B6.lpr and B6.WT mice. A 22 month observation of 226 DKO and 137 B6.lpr mice demonstrated significantly more frequent proliferative glomerulonephritis, larger skin lesions and shorter survival in DKO than in B6.lpr mice. Conversely, microglial activation and cerebral demyelination were less pronounced while long-term synaptic plasticity, was superior in DKO mice. Splenic Th17 cells were significantly higher in DKO than in B6.lpr and B6.WT mice while Th1 and Th2 cell frequencies were comparable between DKO and B6.lpr mice. IL-10 and IL-17 expression by T cells was not affected but there were fewer IL-10-producing myeloid (CD11b+) cells, and also lower serum IL-10 levels in DKO than in B6.lpr mice. The absence of CD137L causes an immune deviation towards Th17, fewer IL-10-producing CD11b+ cells and reduced serum IL-10 levels which potentially explain the more severe lupus in DKO mice while leading to reduced microglia activation, lesser cerebral damage and less severe neurological deficits.